SOME Municipal de Moju/PA: BNCC e Currículo de História - CAMPOS, Wellington Rodrigo de (Universidade Federal do Pará, 2025)
With the rise of the BNCC, in 2017, it was up to the municipalities to adapt to the new curricular guidelines, and in Moju it was no different, with the Municipal Curricular Document approved definitively in 2022. This dissertation aims to discuss the curriculum adopted by History teachers at the municipal SOME of Moju/PA before and after the approval of the BNCC, and subsequently with the introduction of the Municipal Curricular Document. To this end, we sought to understand through Oral Life History the conception of history teachers about the construction of their curricula and which contents were considered most relevant for this construction. As well as understanding the references requested by teachers, observing the subjectivities during their teaching careers, to do so, we must understand that the SOME school environment corresponds to Rural Education and all the complexity that this type of education has with the blocking of workload, the location of the teacher and the usual deficiencies of rural schools in the interior of the Amazon. Through this analysis, it became clear to the interviewed teachers that there are important absences in the prescribed municipal curriculum, such as the distance between Local History and education developed in the countryside, given that the Mojuense countryside is home to a rich and complex history of social struggles and disputes over land ownership.